Strategi Peningkatan Kualitas Literasi Digital Pada Masyarakat - Lilis Suminar; Nissa Maulida; Ichsan Fauzi Rachman (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to explore digital literacy learning strategies aimed at the general public, with a focus on responsible use of technology, as well as overcoming social inequalities that occur in society. Apart from that, digital literacy learning also has a role in supporting the quality of people's understanding of digital media in the era of industrial revolution 4.0 which is marked by advances in the fields of knowledge and technology which will also have an impact on the world of work. This research uses a literature review method to collect and analyze various relevant sources, including journals, books and scientific articles related to digital literacy and implementation strategies in society. It is hoped that the results of this review will provide insight into effective strategies in educating the public about digital literacy, as well as emphasizing the importance of awareness in the use of technology. Thus, this research contributes to providing a strong theoretical basis for the development of comprehensive and responsible digital literacy education programs.